Zero Dengue Health Carnival "Satu Gigitan Seribu Sesalan, Satu Tindakan Seribu Perlindungan" - Abd Malek, Ahmad Afiq; Norman, Fatimah Zahra; Isa, Mohamad Rodi; Ismail, Nurhuda; Xin Wee, Chen (Faculty of Medicine, 2024)
A health carnival entitled ‘Karnival Sifar Denggi’ was held at the MBSA Seri Pagi Hall in Paya Jaras on 12 October 2024, with a slogan of ‘Satu Gigitan Seribu Sesalan, Satu Tindakan Seribu Perlindungan’.